Pengembangan Sistem Informasi Penjualan Laptop, PC, dan Tablet Berbasis Web dengan Metode Prototype untuk Mendukung Layanan COD di Kabupaten Nabire - Gunawan Prayitno; Isak Boas Samanui; Usman Arfan (STIKOM Tunas Bangsa Pematangsiantar, 2025)
This research focuses on the development of a Web-Based Information System for Selling Laptops, PCs, and Tablets using the Prototype method to support Cash on Delivery (COD) services in Nabire Regency. The objective of this study is to create an effective, efficient, and secure sales system that enhances customer convenience and trust in transactions. The Prototype method was applied to ensure the system development process remained adaptive to user requirements through iterative design and testing cycles. The system includes key features such as a homepage, login page, user registration (sign-up), order confirmation, order list, and an order information page that can be printed. System testing was conducted using the black box testing method based on scenarios derived from the use case and activity diagrams. The results indicate that all system functionalities work as expected. This system not only simplifies the electronic device purchasing process but also provides a solution tailored to the local community's preference for COD transactions.